ROLE OF MEDICAL INTERVENTION IN DECIDING SURVIVAL PERIOD IN ROAD TRAFFIC ACCIDENTS INVOLVING FATAL HEAD INJURY (Journal of Forensic Medicine & Toxicology, 2015)
World is facing two major wars now days, civil and criminal war on one hand where as road war on other hand. Every invention has its merits & demerits all depend upon how legitimately we are using them, we should never be under control on these inventions. Though there are tremendous benefits of the roads & vehicles, there are certain drawbacks & dark side began to emerge as congestion increases on roads. over 1.2 million people die each year on the world’s roads. And between 20 & 50 million people suffer non-fatal injuries, in most regions of world this epidemic of road traffic injuries is still increasing.(1) according to WHO data deaths from road traffic injuries account for around 25% of all deaths from injury.(2) WHO’s south east Asia region alone bears 31% of worlds burden of injury & 27% of injury related mortality. (3) in India road traffic injury projected to become 2nd leading cause of death by year 2020 (4) with a registered motor vehicle population of 174 lakh, the state of Maharashtra accounted for largest share (12.3%) of total registered motor vehicles in the country.(5). Maharashtra accounting for 9.3% of country’s population has reported almost 1/6th of accidental deaths due to unnatural cause 16.7% .(6). Head injury associated with traumatic brain injury occurs with the incidence of 20-40 cases per 100000 populations per year. It is most common cause of death in young adults (age 15-24 yrs) and is more common in males than females.(7). Survival of head injury victims depends on how effective and how specialized treatment they have obtained. Present study is aimed at studying role of medical interventions in prolonging life span of victims. And suggestions for preventing road traffic accidents and their effective managements.
Keywords: Head injury; Road traffic accident; Survival period